Characterization of Biofilm production and quorum sensing phenomenon among antibiotic resistant Acinetobacter baumannii isolated from wound infections in Iraq - Rawa Abdul Redha Aziz; Sawsan Sajid Al-Jubori (Journal of Global Pharma Technology, 2017)
Objective(s): Acinetobacter baumannii has emerged as a significant hospital pathogen, quickly becoming resistant to wide range of antimicrobials. It has gained notoriety as a cause of debilitating soft tissue infections in soldiers returning from Iraq and Afghanistan.This study focused on the characterization of biofilm production in Iraqi A. baumannii and its regulation by quorum sensing. Material and Methods: twenty four isolates were collected from Baghdad and Al-Najaf hospitals and re-diagnosed by compact Vitek 2 and genetically using housekeeping gene (recA). Phenotypic detection of biofilm formation was screened by microtiter dish assay, twitching motility assay, and SEM. Quorum sensing phenomenon (QS) was detected using conventional PCR. Results: 100% of isolates formed either strong or weak biofilm by microtiter dish assay. Twitching motility test revealed that 79.2% of isolates were motile. SEM analysis showed 79.2% of isolates made different stages of biofilm started with adhesion step and ending with a mushroom like architecture as highly magnification images showed on glass cover slips. PCR analysis of QS showed that 91.7% of A. baumannii harbored AHL gene encoding N-acyl homoserine lactone hydrolase at amplified size 498bp, while 83.3% of A. baumannii isolates could harbor abaI gene encoding N-acyl homoserine lactone synthase at amplified size 382bp. Conclusion: it could be concluded that A. baumannii isolates were capable to produce biofilm and control it using quorum sensing genes expression. This would raise the concern of dissemination of chronic infections among hospitalized patients in two cities: Baghdad and Al-Najaf.